Solving a weighty problem: Systematic review and meta-analysis of nutrition interventions in severe mental illness - Teasdale, Scott B.; Ward, Philip B.; Rosenbaum, Simon; Samaras, Katherine; Stubbs, Brendon (British journal of psychiatry, 2017)
Nutrition interventions would appear fundamental for weight management and cardiometabolic risk reduction in people experiencing severe mental illness (SMI). Comprehensive evaluation of nutrition interventions is lacking. To subject randomised controlled trials of nutrition interventions in people with SMI to systematic review and meta-analysis, and to measure anthropometric and biochemical parameters and nutritional intake. An electronic database search identified trials with nutrition intervention components. Trials were pooled for meta-analysis. Meta-regression analyses were performed on anthropometric moderators. Interventions led to significant weight loss (19 studies), reduced body mass index (17 studies), decreased waist circumference (10 studies) and lower blood glucose levels (5 studies). Dietitian-led interventions (6 studies) and studies delivered at antipsychotic initiation (4 studies) had larger effect sizes. Evidence supports nutrition interventions as standard care in preventing and treating weight gain among people experiencing SMI.